On Spiritual Subjects: Negotiations in Muslim Female Spirituality - Seedat, Fatima (African Journal of Gender and Religion, 2022)
This paper applies reading strategies adapted from feminist philosophy to the discursive construction of women as spiritual subjects in a Sufi narrative. The aim of this reading is first, to show the challenge women’s spiritual excellence presents to normative representations which privilege male spirituality, and then to illustrate the ways in which women’s spiritual excellence is negotiated in the text, at times challenging but generally reaffirming patriarchal distinctions between masculinity and femininity. To do this, the paper offers a deep reading of Farīd al-Dīn ‘Aṭṭār’s textualization of Rabī’a al-’Adawiyya using the cosmological gender of Sufi thought and reading methods drawn from feminist philosophy. It reads the male/female duality of ‘Aṭṭār’s text for the assumptions, the imaginaries and metaphoric networks, and the silences that inform the representations of Muslim female spirituality. In ‘Aṭṭār’s construction of a metaphoric spiritual masculinity, we are made to see Rabī’a’s spirituality as an illustration of gender performance. Even though he does not go as far as we might want, ‘Aṭṭār shows us how it is possible to be in the way that men “naturally” are while being embodied as women “naturally” are. In casting a woman as a man Aṭṭār appeals to the subtext of a Sufi cosmology of genders, to metaphors of masculinity and femininity and to ideas of affect and receptivity in order to construct a body such as Rabī’a’s in masculine ways. Thus, he pays homage to Rabī’a’s spiritual agency, and that of other women like her, but does so without relinquishing the spiritual superiority that he associates with the male body. The effect of the analysis is to illustrate the complex and contested representation of female spirituality in Islamic thought, and in doing so to also locate contemporary negotiations of female spiritual agency along an historical trajectory of negotiation.